Diabetes self-care maintenance, comorbid conditions and perceived health - Song, M; Lee, CS (International Diabetes Nursing, 2009)
Abstract Background: The rising global prevalence of diabetes mellitus (DM) has made it increasingly important for healthcare providers to examine how amenable factors beyond optimal medical care might influence health outcomes. DM self-care maintenance (SCM) is an important influential component of overall care, and perceived health is an important subjective health outcome. However, the relationship between DM SCM and perceived health has not been examined extensively. Aim: To study the relationship between DM SCM and perceived health. Methods: A secondary analysis was performed using cross-sectional descriptive self-reported data from 1154 adults with DM living in Pennsylvania. Multivariate hierarchical logistic regression modelling was used to determine whether better SCM was significantly associated with better perceived health, controlling for the influence of sociodemographics and comorbid conditions. Results: Higher levels of engagement in SCM (healthier diet and more exercise) were significantly associated with better perceived health. Three comorbid conditions included in the model were associated with worse perceived health. Conclusion: Our data suggest that interventions designed to improve outcomes for patients with DM should take into account the relationship between SCM and perceived health. Although further research is needed to replicate our findings in more heterogeneous patient populations, nurses should consider improving SCM as a means of improving health outcomes, such as health status in patients with DM.